THE EFFECT OF GROWTH OPPORTUNITY AND LIQUIDITY ON FIRM VALUE WITH PROFITABILITY AS A MODERATING VARIABLE - Kartika, Rika (Yayasan Education and Social Center, 2024)
The purpose of this research is to partially analyze and partially determine the influence of opportunity and liquidity on company value and partially analyze and determine the influence of opportunity and liquidity on firm value with profitability as a moderating variable. The population in the study was 47 food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2022 period, with a total sample size of 38 sample data. The analysis used in this research is Moderated Regression Analysis (MRA) using SPSS 26 software. The results of this research are that partially extensive opportunity influences firm value; partially liquidity has no effect on firm value, profitability cannot moderate ample opportunities on firm value, and profitability can moderate liquidity on firm value. These results indicate that increasing the profitability value can strengthen the company's liquidity and increase the firm's value